The Impact of Electronic Service Quality Dimensions and Promotion on Consumer Purchase Decisions in Online Shopping Through Shopee E-Commerce - Marlita, Maya; Fihartini, Yuniarti (LPPPIPublishing, 2026)
Where practicality and efficiency are top priorities, particularly in the online shopping phenomenon. This has fueled the exponential growth of e-commerce in Indonesia, with Shopee as one of the platforms dominating the market. Despite its success, Shopee faces significant challenges related to the complexity of its interface design, personal data security concerns, and the effectiveness of promotions that are perceived as intrusive or too short-lived. This study aims to analyze the influence of e-service quality dimensions—consisting of website design, customer service, security/privacy, and fulfillment—and promotional variables on consumer decisions. The research method used was quantitative with a causal approach. Data were obtained through purposive sampling of 130 respondents residing in Bandar Lampung City. Data analysis was conducted using multiple linear regression using IBM SPSS Statistics 27.0 software, supplemented by a coefficient of determination (R2) test and a partial t-test. The results showed that website design, customer service, security/privacy, fulfillment, and promotions partially had a positive and significant influence on consumer decisions. Simultaneously, these variables explained 81.1% of the variation in consumer decisions. The implications of this study suggest that to improve purchasing decisions, Shopee needs to optimize ease of navigation, improve the integrity of product condition upon arrival, and strengthen data security assurance to build sustainable consumer trust.